Renewable energy policy and politics : a handbook for decision-making / edited by Karl Mallon. - Mallon, Karl (Earthscan, 2004)
'Effective Renewable Energy Policy' examines the renewable energy sector and its stakeholders, analysing the reasons for past failures and the key features of successful policies.